Sex-related differences in spontaneous intracerebral hemorrhage outcomes: A prognostic study based on 111,112 medical records - Zhao, Jieyi; Zhang, Tao; Wan, Hongli; Yu, Yang; Wen, Jin; Wang, Xiaoyu (Frontiers in Neurology, 2022)
Objective To identify sex-related differences in the outcome of hospitalized patients with spontaneous intracerebral hemorrhage (SICH), and to identify potential causal pathways between sex and SICH outcome. Methods A total of 111,112 medical records of in-hospital patients with SICH were collected. Data- and expert-driven techniques were applied, such as a multivariate logistic regression model and causal mediation analysis. These analyses were used to determine the confounders and mediators, estimate the true effect of sex on the SICH outcome, and estimate the average causal mediation effect for each mediator. Results (1) Failure (disability or death) rates in women with SICH were significantly lower than in men with SICH. On the day of discharge, the odds ratio (OR) of failure between women and men was 0.9137 [95% confidence interval (CI), 0.8879–0.9402], while the odds ratio at 90 days post-discharge was 0.9353 (95% confidence interval, 0.9121–0.9591). (2) The sex-related difference in SICH outcome decreased with increasing age and disappeared after 75 years. (3) Deep coma, brainstem hemorrhage, and an infratentorial hemorrhage volume of >10 ml accounted for 62.76% (p < 0.001), 33.46% (p < 0.001), and 11.56% (p < 0.001) of the overall effect on the day of discharge, and for 52.28% (p < 0.001), 27.65% (p < 0.001), and 10.86% (p < 0.001) of the overall effect at the 90-day post-discharge. Conclusion Men have a higher failure risk than women, which may be partially mediated by a higher risk for deep coma, brainstem hemorrhage, and an infratentorial hemorrhage volume of >10 ml. Future work should explore the biological mechanisms underlying this difference.